GPS decoder - Tan, Eng Chong; Abdul Rahman, Abdul Wahab; S., E. Hong (1997)
The paper describes a low-cost hardware design of a GPS decoder that is compact enough to be installed inside a vehicle. The decoder operates on a portable power supply or car battery and obtains raw tracking data (positionlvelocity) from a GPS receiver for processing. It can be easily interfaced with a microcomputer to perform specific application such as road mapping using graphical-user-interface (GUI) software program.